Benign symmetrical lipomatosis type II in 52-year-old patient – a case report and review of literature - Gibała, Magdalena; Janowski, Grzegorz; Cisowska, Grażyna; Juza, Anna; Książek, Mariusz; Gutkowski, Krzysztof (European Journal of Clinical and Experimental Medicine, 2015)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Benign Symmetrical Lipomatosis – BSL also called Madelung disease or Launois-Bensaude syndrome is a rare medical condition of unclear etiology which is characterized by symmetrical, progressive growth of adipose tissue. This disease mostly affects males between ages of 30 and 60 living in the Mediterranean region and eastern European countries. In about 90% of cases there is dependency between alcohol abuse and emergence of disease’s symptoms. Excess of the adipose tissue is most often accumulated around the neck area causing dyspnea and swallowing disorders. More rarely the adipose tissue is excessively stored in other parts of occasionthe body except for distal parts of upper and lower limbs. The basis to diagnose the disease is physical examination in correlation with data from anamnesis. Imaging and histopathological examination of the adipose tissue taken from places of its excessive development are helpful in diagnosis. Patients affected by BSL also often suffer from liver cirrhosis, disorder of carbohydrate metabolism, hyperlipidaemia and hyperuricaemia, impairment of renal tubules and abnormalities in blood count. The only way of treatment is surgical excision of excessively developed adipose tissue or liposuction. In this study a case of benign symmetrical lipomatosis in a 52-year-old female patient is presented together with synthetic literature review.